Profiles of muscularity in junior Olympic weight lifters - Kanehisa, H.; Funato, K.; Abe, T.; Fukunaga, T. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: This study aimed to investigate the muscularity of strength-trained junior athletes. Methods: Muscle thickness (Mt) values at 10 sites (anterior forearm, anterior upper arm, posterior upper arm, chest, abdomen, back, anterior thigh, posterior thigh, anterior lower leg, and posterior lower leg) were determined in junior Olympic weight lifters (OWL, n=7, 15.1±0.3 y, mean±SD) and non-athletes (CON, n=13, 15.1±0.3 y) using a brightness mode ultrasonography. Skeletal age assessed with the Tanner-Whitehouse II method (20 hand-wrist bones) was similar in OWL (16.4±0.7 y) and CON (16.3±0.6 y). Results: At the 6 sites (anterior forearm, anterior upper arm, posterior upper arm, chest, back and anterior thigh), OWL showed significantly greater Mt values than CON even in terms of Mt relative to (body mass)1/3 (Mt·BM-1/3). On the other hand, there were no significant differences between the 2 groups in the Mt ratios of the anterior to posterior site in the upper arm, thigh and lower leg and those of the back to either the chest or abdomen in the trunk. For OWL only, skeletal age was significantly correlated to Mt·BM-1/3 at the abdomen (r=0.869, p<0.05) and anterior thigh (r=0.883, p<0.05). Conclusion: The findings here indicate that 1) as compared to adolescent non-athletes, junior Olympic weight lifters show a greater muscularity in the upper body and anterior thigh without predominant development in either of anterior and posterior sites within the same body segment, 2) for junior Olympic weight lifters, the muscularity of abdominal and knee extensor muscles is influenced by the biological maturation.